2012
DOI: 10.1111/j.1365-2125.2012.04310.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in cardiovascular drug‐induced adverse reactions causing hospital admissions

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Cardiovascular disease, disease outcome, drug treatment and drug response differ between men and women. WHAT THIS STUDY ADDS• Adverse drug reactions attributed to cardiovascular drugs that require hospital admission show differences between men and women, even after taking into account age and the total number of drug prescriptions. AIMSCardiovascular disease in women is often underestimated. The effects of cardiovascular drugs differ between the sexes because of pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 58 publications
2
30
1
Order By: Relevance
“…The reported median prevalence rates for MRPs were similar in retrospective ( n = 5) and prospective studies ( n = 13; Table ). The five retrospective studies showed a median prevalence rate of 12.6% (IQR, 10.8–13.3%).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The reported median prevalence rates for MRPs were similar in retrospective ( n = 5) and prospective studies ( n = 13; Table ). The five retrospective studies showed a median prevalence rate of 12.6% (IQR, 10.8–13.3%).…”
Section: Resultssupporting
confidence: 53%
“…Old age and polypharmacy were the main risk factors reported in most studies. Furthermore, some studies reported gender as a risk factor; females were more likely to develop MRPs . Fewer studies reported depression (three studies) , education (two studies) , cohabitation (two studies) and immobilization (one study) as risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…During the 4-year study period, we observed an increase in the incidence of anticoagulant-related hospitalisations, which was greater in men than in women for all age groups. These data are consistent with those reported by Rodenburg et al ,32 whose objective was to identify possible differences in ADRs to cardiovascular drugs between men and women over a 6-year period. The authors found that admissions for ADRs to anticoagulants and salicylates were more common in men (RR 0.94; 95% CI 0.90 to 0.98).…”
Section: Discussionsupporting
confidence: 91%
“…Further, the same increase in cardiac output increases renal artery blood flow, and the clearance of xenobiotics is also an influential factor. Overall, despite variables that account for gender differences in the pharmacokinetics of metoprolol, the findings in this article show a 50% dose reduction results in equivalent metoprolol exposure to men and may help to explain and remedy the findings from studies reporting women who experience greater adverse effects related to cardiovascular medications than men [6,15,16]. With the hopes of precision medicine, dose adjustments based on gender, genotype, or both will become increasingly sought after by clinicians in medical practice and patients being administered these medications.…”
Section: Discussionmentioning
confidence: 88%